PENGARUH BAHAN AJAR DAN MINAT TERHADAP PRESTASI BELAJAR (Studi Eksperimen pada Mata Pelajaran Kimia Siswa Kelas XII IPA di SMA Negeri 1 Pagar Alam) - Erna Susrini (DIADIK, 2021)
This study aims to examine the difference between the learning achievement of students who study with e-module teaching materials and students who study using textbooks, the difference in learning achievement of students who have high interest and students who have low interest, the interaction between teaching materials and student interest. on learning achievement. The design used in this study is a quasi-experimental design with a 2 x 2 factorial design. The research population is all students of class XII MIPA SMA Negeri 1 Pagar Alam for the academic year 2020-2021 which consists of 6 classes. The class sampled in the experimental group was class XII MIPA 1 and the control class was class XII MIPA 3. The sample was selected using purposive random sampling technique. Data were collected by means of a learning achievement test in the form of multiple choice and a questionnaire for interest in learning. The collected data was statistically processed using the two-way analysis of variance (ANAVA) technique using a significance level of 5%. The results showed that: the learning achievement of students who were taught using e-module teaching materials was higher than that of textbooks, the learning achievement of students who had high interest in learning was higher than that of students who had low interest, there was an interaction between teaching materials. and interest in learning towards learning achievement